Efektivitas Sistem Informasi di Bank Perkreditan Rakyat: Ekplorasi Pengaruh Kemajuan Teknologi Informasi, Kompetensi Pengguna dan Kepuasan Pengguna Sistem Informasi Akuntansi - Ketut Tanti Kustina; Ida Ayu Putu Dyah Medianasuari; Gusi Putu Lestara Permana; I. G. A Diah Utari (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
This study aims to determine how the effectiveness of accounting information systems at BPRs is influenced by information technology sophistication, user competence, user participation, and user satisfaction. Covered sampling was implemented to choose the sample for a study in Gianyar Regency that involved 70 BPR personnel who used accounting information systems as their study population. Multiple linear regression was applied as a method of data analysis together with the survey filling method. After analyzing statistical analysis using the SPSS software application, the results indicate a significant and positive indicator of information technology sophistication, user competence, user engagement, and user satisfaction on the effectiveness of the accounting information system.